2021
DOI: 10.3390/agriculture12010006
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Drought Tolerance of Miscanthus Genotypes through Dry-Down Treatment and Fixed-Soil-Moisture-Content Techniques

Abstract: Miscanthus, a high-yielding, warm-season C4 grass, shows promise as a potential bioenergy crop in temperate regions. However, drought may restrain productivity of most genotypes. In this study, total 29 Miscanthus genotypes of East-Asian origin were screened for drought tolerance with two methods, a dry-down treatment in two locations and a system where soil moisture content (SMC) was maintained at fixed levels using an automatic irrigation system in one location. One genotype, Miscanthus sinensis PMS-285, sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…Second generation biofuel crops are promising candidates for sustainable cultivation on marginal lands (Pancaldi & Trindade, 2020), especially C4 perennials such as miscanthus and switchgrass. Nonetheless, several studies on both crops reported a substantial decrease in yield under drought (Barney et al, 2009; Berdahl et al, 2005; Weng et al, 2022). Enhancing tolerance, however, ensures yield stability; a prerequisite for economically viable exploitation of drought‐affected lands for bioenergy production (Ings et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Second generation biofuel crops are promising candidates for sustainable cultivation on marginal lands (Pancaldi & Trindade, 2020), especially C4 perennials such as miscanthus and switchgrass. Nonetheless, several studies on both crops reported a substantial decrease in yield under drought (Barney et al, 2009; Berdahl et al, 2005; Weng et al, 2022). Enhancing tolerance, however, ensures yield stability; a prerequisite for economically viable exploitation of drought‐affected lands for bioenergy production (Ings et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This presents a major obstacle for its adoption on a wider commercial scale given its costly plot setup via rhizome propagation (Xue et al, 2015), in addition to hindering its optimization via breeding (Jakob et al, 2009). Alternatively, the seedbased M. sinensis is gaining interest as a suitable replacement, owing to its genetic diversity (Clifton-Brown et al, 2017;Sacks et al, 2013), better tolerance to abiotic stresses (Clifton-Brown & Lewandowski, 2000a;Weng et al, 2022), and generally lower cell wall lignin contents (Qin et al, 2012;van der Weijde et al, 2017a). The latter is strongly associated with a higher saccharification efficiency (Van der Weijde et al, 2017c;Zhao et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations